1986
DOI: 10.1037/0021-843x.95.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of fear-reducing behavior: Relevance for the conditioning theory of neurosis.

Abstract: The present study provided experimental support for Mowrer's conditioning theory of neurosis. Naive hooded rats were given fear-conditioning (CS-shock) trials in one side of a two-compartment apparatus. Then, in the absence of shock, they were allowed to escape fear by jumping a hurdle to a safe compartment. The hurdle-jumping response was considered to be analogous to anxiety-based symptomatic behavior indicative of psychopathology in that the performance of the response was unrelated to the receipt of furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…The dominant reaction of the rat to a feared context is freezing (Fanselow & Lester, 1988), even when the rat has been given ample time to learn that escape routes are available. When escape speeds are used to measure context fear, those speeds are often very slow at fi rst, and they reach their maximum only after about 50 escapes (McAllister, McAllister, Scoles, & Hampton, 1986). Our frightened rats failed to escape rapidly because they were freezing.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant reaction of the rat to a feared context is freezing (Fanselow & Lester, 1988), even when the rat has been given ample time to learn that escape routes are available. When escape speeds are used to measure context fear, those speeds are often very slow at fi rst, and they reach their maximum only after about 50 escapes (McAllister, McAllister, Scoles, & Hampton, 1986). Our frightened rats failed to escape rapidly because they were freezing.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance to Extinction As was noted above, many studies have shown remarkable persistence of the avoidance response (Levis, 1966;Levis et al, 1970;Levis & Boyd, 1979;Logan, 1951;Malloy & Levis, 1988;McAllister et al, 1986;Seligman & Campbell, 1965;Wahlsten & Cole, 1972; R. W. Williams & Levis, 1991). For example, reported that with 200 extinction trials none of the dogs in their experiment extinguished the response.…”
Section: Variability In the Resistance Ofmentioning
confidence: 99%
“…Neither of these predictions corresponds to the empirical findings. Instead, once the avoidance response is well learned, animals often continue to perform it in every trial, during both acquisition and extinction (Levis, 1966;Levis, Bouska, Eron, & McIlhon, 1970;Levis & Boyd, 1979;Logan, 1951;Malloy & Levis, 1988;McAllister, McAllister, Scoles, & Hampton, 1986;Seligman & Campbell, 1965;Wahlsten & Cole, 1972; R. W. Williams & Levis, 1991). Furthermore, avoidance responding persists, and even gets stronger, after fear of the CS is drastically reduced or even nearly extinguished Mineka, 1979;Rachman, 1976;Riccio & Silvestri, 1973).…”
Section: Findings Inconsistent With Two-factor Theorymentioning
confidence: 99%
“…This finding may be attributable to some modification's having occurred in the subject during original conditioning. Rapid reconditioning has been found not only with the fear response in rats (e.g., D. E. McAllister & W. R. McAllister, 1994;W. R. McAllister et al, 1986), but also with the nictitating membrane response in rabbits (e.g., Macrae & Kehoe, 1999;Napier, Macrae, & Kehoe, 1992;Weidemann & Kehoe, 2003), the heart rate response in rabbits (e.g., Weidemann & Kehoe, 2003), and the eyelid response in rabbits (e.g., Medina, Garcia, & Mauk, 2001).…”
mentioning
confidence: 99%
“…First, if some time elapses after a behavior has ceased, an extinguished conditioned fear response may recover spontaneously, so that the behavior is again supported (e.g., W. R. McAllister, D. E. McAllister, Scoles, & Hampton, 1986). Second, if fear is conditioned separately to two stimuli and then fear to each stimulus is extinguished to a level that does not support a behavior, presenting the two stimuli together can lead to the restoration of that behavior (Hendry, 1982;Reberg, 1972).…”
mentioning
confidence: 99%